Hubungan Karakteristik Bawahan, Kontrol Situasi, Gaya Kepemimpinan, Budaya Organisasi, dan Iklim Organisasi dengan Keefektifan Organisasi di Universitas Swasta - Hendyat Soetopo (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This study was focused on the organization effectiveness of private universities. Data were collected using a questionnaire administered to 263 lecturers of private universities in Malang Municipality drawn randomly. The data were then analyzed statistically by percentages, mean measures, dan path analysis. The results indicated that there were 7 components of organizational effectiveness: communication system, goal setting, leadership process, decision-making process, motivation intensity/strength, controlling process, and interaction process. In general, there was a correlation between subordinates' characteristics, situation control, leadership style, organization culture, organization climate, and the organization effectiveness of the private universities.